Rhinoscleroma - Raymundo, Igor Teixeira; Pádua, Sharlene Castanheira; Pinheiro, Thaís Gonçalves; de Azevedo, Ana Emília Borges; Nakanishi, Márcio; de Oliveira, Carlos Augusto Costa Pires (Arquivos Internacionais de Otorrinolaringologia, 2011)
Introduction: Rhinoscleroma is a chronic granulomatous infectious disease caused by the bacterium Klebsiella rhinoscleromatis. It affects the respiratory tract mucosa, most frequently in the nose. It is considered endemic to certain countries of Africa and Central America, but is rare in Brazil. Nasal involvement occurs in 3 phases: catarrhal, granulomatous, and sclerotic. Throughout its course, the disease presents nonspecific symptoms, making it difficult to diagnose. Diagnosis is established by culture or by anatomopathological observation of Mikulicz cells or Russell corpuscles. Treatment consists of long-term antibiotic therapy and, occasionally, surgery.Objective: We report a case of rhinoscleroma in a young woman who complained of obstruction in both nostrils and persistent headache. Our intent is to enable otorhinolaryngologists to diagnose this rare disease, which presents with nonspecific symptoms that resemble numerous pathologies of the nasal region.
Keywords: rhinoscleroma; klebsiella infections; nasal acquired rhinoscleroma